Excellent strength-ductility synergy of NiAl-based composites achieved by a 3-dimensional network structure. (15th January 2022) - Lu, Zhen; Liu, Dekai; Shi, Chengcheng; Xiao, Han; Liu, Wei; Jiang, Shaosong
Abstract: NiAl intermetallic compounds have attracted the attention of researchers in the field of high-temperature structural materials, but their poor room-temperature ductility and insufficient high-temperature strength crying out for solutions have hindered their practical application. To solve these problems, a novel 3-dimensional network structure-reinforced NiAl-based composite was designed by hot presing sintering sinter with pre-alloyed powders. The 3-dimensional network structure was composed of discrete nearly spherical HfO2 and rod-shaped HfRe2 . The mechanical properties of the composites were closely correlated with the distribution of the 3-dimensional network structure in the matrix, which was controlled by the sintering temperature and holding time. A microstructure with a desirable 3-dimensional network structure distribution and the best comprehensive mechanical properties was produced at 1375 °C/60 min. The microstructural evolution along with the strengthening and toughening mechanisms were discussed in detail. The increase in the high-temperature strength was mainly attributed to the pinning effect of the 3-dimensional network structure on dislocations and the restraining effect on the sliding and rotation between the matrix grains, while the increase in room-temperature ductility was mainly due to the grain refinement and hindering of crack propagation by the 3-dimensional network structure. In this paper, the development of a novel low-density NiAl-based composite with a 3-dimensional network structure improved both the strength and ductility, providing design ideas for the application of NiAl-based materials.